Pengaruh Investasi Asing Langsung (FDI), Tenaga Kerja dan Sektor Pertanian Terhadap Pertumbuhan Ekonomi di Negara D-8 (Developing Countries) - Abdul Gani Laraga; Silvy Windha Mediaswari (Tirtayasa Ekonomika, 2025)
ABSTRACTThis study aims to examine the impact of Foreign Direct Investment (FDI), labor, and the agricultural sector on economic growth in D-8 (Developing Countries) member states during the 2013-2021 period. Based on the results of panel data regression using the Fixed Effect Model (FEM), it was found that only FDI and the agricultural sector had a positive influence on economic growth. Conversely, the labor variable was found to have no impact on economic growth in the D-8 countries under observation during the study period. Therefore, governments need appropriate macroeconomic policies to accelerate economic growth in D-8 countries, considering the benefits of GDP as an instrument for boosting a nation's economy.